Capital Structure in Transition: The Transformation of Financial Strategies in China's Emerging Economy - Keister, Lisa A. (Organization Science, 2004)
During economic transition, firms must dramatically reduce their financial dependence on the state and begin to borrow from nonstate capital sources. This paper draws on institutional and resource dependence theories to examine this fundamental transformation of firm capital structure during China's transition. I propose that managers borrowed from external sources even when internal funds were available because retained earnings were considered state assets. Firms used retained earnings to signal financial health but borrowed externally to reduce dependence on the state. Uncertainty during transformation produced interfirm imitation of borrowing strategies, particularly imitation of local and high status others. I argue that the dynamics of market development shaped firm borrowing strategies and that these strategies are best viewed as trajectories over time. Analysis of survey data on the 1980–1989 capital structure of formerly state-owned firms provides support for these arguments and highlights the importance of institutional context in understanding corporate borrowing and strategic decision making.